A poor inquiry: Poverty and living standards in pre-famine Ireland - Áine Doran (Queen's University Centre for Economic History (QUCEH), 2021)
This paper studies the relationship between pre-famine living conditions and famine severity. I digitise the parish-level returns of the Irish Poor Inquiry and use these to explain the co-variates of increasing poverty in the early nineteenth century and examine how they impacted the severity of The Great Famine. I find that income acted as a key co-variate of increasing poverty, with the poor becoming poorer. However, it is levels, not changes, of poverty which are found to be a key determinant of famine severity, alongside the structural features of parishes, such as their distance from the nearest navigable waterway. The paper also fails to find evidence of increasing poverty or famine severity being a result of overpopulation.
Keywords: J10; I32; N33; 330; poverty; living conditions; famine; Ireland; demography